Making sense of data ethics. The powers behind the data ethics debate in European policymaking - Gry Hasselbalch (Internet Policy Review, 2019)
This article offers an analytical investigation of the different actors and forces that mould definitions of "data ethics" in European policy-making. It details how data ethics public policy initiatives took shape in the context of the European General Data Protection reform, and addresses the general uncertainty that exists regarding their role and function. The paper also presents an analytical framework for an action-oriented "data ethics of power" that aims to elucidate the power relations of the 'Big Data Society', arguing that we recognise data ethics policy initiatives as open-ended spaces of negotiation among different interest groups that seek to guide the cultural definition of "data ethics", with complex power relations exercised via cultural positioning.
Keywords: 300; Data ethics; Data protection; Privacy; European policymaking; Governance